Livestock Farming in Bashkiria in 1946-1950: Dynamics of Production of Main Types of Products - V. P. Motrevich; V. N. Mamyachenkov (Научный диалог, 2024)
The article examines the dynamics of livestock production in the individual and collective sectors in the Bashkir ASSR during the first postwar five-year period (1946-1950). Archival data is introduced into scientific circulation. Emphasis is placed on the fact that throughout the studied period, the recovery of livestock farming in the republic faced significant challenges. Information is provided on the production of main types of livestock products during the fourth five-year plan by specific categories in natural and monetary terms. It is noted that the pre-war level of production volume was never reached in various indicators: the number of cattle, sheep, goats, and horses, gross production of eggs, wool, honey, etc. Among the socio-economic reasons hindering the development of livestock farming in the republic are cited: consequences of World War II; low state investment in agriculture; low level of livestock technologies; deliberate policy by authorities viewing agriculture as an appendage to industry; low living standards of rural residents. The contribution of Bashkiria to the country’s food balance is determined. The conclusion is drawn that the individual sector of livestock farming, despite extremely unfavorable conditions and resistance from government authorities in the first post-war five-year period, overall maintained its positions and produced over 2/3 of the livestock products in the republic.